ADVANCED-DATA ACQUISITION AND AUTOMATED MONITORING SYSTEMS IN RAILWAY SAFETY - Sridevi Palepu, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Advanced data acquisition and automated monitoring systems represent a transformative advancement in railway safety and operational efficiency. Integrating sophisticated train control technologies, TETRA protocols, and nanosensor implementations has revolutionized track maintenance and safety protocols. Through the deployment of multi-tiered monitoring frameworks incorporating ultrasonic B-scan detection, RFID tracking, and mobile inspection platforms, railway networks have achieved enhanced defect detection capabilities and improved resource utilization. Implementing machine learning algorithms and real-time data processing has enabled proactive maintenance strategies, while integrated GPR and InSAR technologies have strengthened track inspection capabilities. These technological advancements have reduced accident rates, optimized maintenance schedules, and improved overall system reliability across railway networks.